2010
DOI: 10.1038/ajg.2010.106
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Children With Functional Abdominal Pain and Their Parents Decreases Pain and Other Symptoms

Abstract: OBJECTIVES Unexplained abdominal pain in children has been shown to be related to parental responses to symptoms. This randomized controlled trial tested the efficacy of an intervention designed to improve outcomes in idiopathic childhood abdominal pain by altering parental responses to pain and children's ways of coping and thinking about their symptoms. METHODS Two hundred children with persistent functional abdominal pain and their parents were randomly assigned to one of two conditions—a three-session in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
214
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(233 citation statements)
references
References 45 publications
11
214
3
5
Order By: Relevance
“…Other studies highlight the importance of parental acceptance of a biopsychosocial model for the explanation of the child's symptoms which was associated with long-term symptom recovery [9,37]. A three-session cognitive-behavioral intervention study by Levy and coauthors [35] aimed mainly at modifying the families' response on illness behavior of the child and could demonstrate a long-lasting reduction of parentreported AP in a large sample. Beyond this, the empowerment of parents to take an active role in their child's treatment might help to reduce helplessness and contribute crucially to treatment success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies highlight the importance of parental acceptance of a biopsychosocial model for the explanation of the child's symptoms which was associated with long-term symptom recovery [9,37]. A three-session cognitive-behavioral intervention study by Levy and coauthors [35] aimed mainly at modifying the families' response on illness behavior of the child and could demonstrate a long-lasting reduction of parentreported AP in a large sample. Beyond this, the empowerment of parents to take an active role in their child's treatment might help to reduce helplessness and contribute crucially to treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it easy and cheap to implement. Although children with AP are affected by this condition from months to years [53], there is growing evidence of the efficiency of very brief psychosocial interventions in treating AP [35,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An innovative approach uses CBT with adolescents with gastrointestinal functional disorders, emphasizing the use of exposure treatment to practice experiencing symptoms in difficult situations, to reduce avoidance behaviors and fear of symptoms (Bonnert et al, 2014). In this case, the role of the parents in helping and reinforcing the exposure component seems critical to the success of the intervention (Levy et al, 2010).…”
Section: Psychological Methods Involvedmentioning
confidence: 99%
“…6,7 The effectiveness of psychological therapies for pediatric FAP has been studied in several randomized controlled trials (RCTs). [8][9][10][11][12][13] Although a recent Cochrane review described cognitive behavior therapy (CBT) as a promising psychological treatment, this review also underscored that many RCTs have considerable methodological drawbacks such as small sample sizes and high dropout rates. 14 Moreover, a well-designed RCT published after the Cochrane review did not provide unequivocal evidence for the benefit of CBT because it showed CBT to be superior to a control condition but only according to parent report of the child' s pain, not according to child-reported pain.…”
mentioning
confidence: 99%